An endoscopic transnasal prelacrimal recess transmaxillary approach to the pterygopalatine fossa and infratemporal fossa - Liu, Jian; Yang, Zhijun; Lu, Bin; Bi, Zhiyong; Liu, Pinan (Frontiers in Surgery, 2023)
Objective In this paper, the goal of the authors is to present the anatomic nuances and their clinical experience with lesions of the pterygopalatine fossa and infratemporal fossa using an endoscopic transnasal prelacrimal recess transmaxillary approach (PLRMA). Methods An endoscopic anatomical dissection of three fresh cadaveric heads was performed bilaterally to evaluate the feasibility of the PLRMA. Prior to dissection, stereotactic computed tomography scans were obtained for each head to obtain anatomical measurements. The area of exposure on the posterior wall of the maxillary sinus was determined using stereotaxis. The cases of six patients with schwannomas or epidermoid cysts who underwent the transnasal PLRMA were illustrated. Results The mean area of exposure on the posterior wall of the maxillary sinus was 9.55 cm2. Total resection was achieved in all six patients. The mean follow-up time was 16 months, and one patient complained of postoperative facial numbness, which resolved gradually. No cases of chronic sinusitis were reported. Conclusions The endoscopic transnasal PLRMA provides efficient operative exposure to the pterygopalatine fossa and infratemporal fossa. Preserving the integrity of the mucosa on the nasal lateral wall is an advantage of this approach.